2020
DOI: 10.1002/ese3.663
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CO2 injection on the pore size distribution and petrophysical properties of tight sandstone cores using nuclear magnetic resonance

Abstract: CO2 injection has been proposed as an efficient method for enhanced oil recovery in low‐permeability sandstone reservoirs. When CO2 is injected into such reservoirs, the petrophysical properties as well as the pore size distribution of tight formation can be altered due to the interactions between CO2, water, and rock minerals. In this work, CO2 is introduced into the water‐saturated sandstone cores; nuclear magnetic resonance technique is then applied to obtain T2 spectrum of the sandstone cores before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The number of dissolution pores increased, the pore size increased, and the porosity and permeability increased after soaking in the CO 2 aqueous solution. Furthermore, Zhao et al 99 showed that CO 2 could dissolve albite, potassium feldspar, dolomite, and calcite After that, the asphaltene precipitation increases slightly with the increased temperature.…”
Section: Tight Reservoirsmentioning
confidence: 99%
“…The number of dissolution pores increased, the pore size increased, and the porosity and permeability increased after soaking in the CO 2 aqueous solution. Furthermore, Zhao et al 99 showed that CO 2 could dissolve albite, potassium feldspar, dolomite, and calcite After that, the asphaltene precipitation increases slightly with the increased temperature.…”
Section: Tight Reservoirsmentioning
confidence: 99%
“…Besides, the interfacial tension between CO 2 and crude oil disappears after CO 2 reaches the miscible pressure, and in this scenario, CO 2 can enter the small pores that cannot be readily swept below the MMP, thereby improving the oil production in small pores . On the other hand, CO 2 and crude oil will undergo a multiple-contact miscible process, and the oil recovery efficiency also depends on the pore structure of reservoir rocks. …”
Section: Introductionmentioning
confidence: 99%
“…40 In addition, when CO 2 injection leads to rupture and slip of the preexisting fault, a new fracture nucleates and progressively propagates, 44 which increase the porosity of the rock. For example, Zhao 45 found that, when the confining pressure is not applied, the porosity of homogeneous sandstones after CO 2 exposure increases by 1.5−2.0%. However, heterogeneity, such as the bedding plane 20 and natural fracture, 17 is common in underground reservoirs.…”
Section: Introductionmentioning
confidence: 99%